Comparison of efficacy of immune checkpoint inhibitors (ICIs) between younger and older patients: A systematic review and meta-analysis - Nishijima, Tomohiro F.; Muss, Hyman B.; Shachar, Shlomit S.; Moschos, Stergios J. (Cancer treatment reviews, 2016)
•This meta-analysis compared the efficacy of ICIs between younger and older patients.•ICIs significantly improved OS in both younger (HR, 0.75) and older (HR, 0.73) groups.•An improvement in PFS was observed in younger (HR, 0.58) and older (HR, 0.77) patients.•In the PD-1 inhibitor subgroup, a significant benefit was not seen in the patients aged ⩾75 years. Immune checkpoint inhibitors (ICIs) rely on the presence of ongoing immune response to exert their antitumor effect. Little is known whether an age-related decline in immune function negatively influences antitumor response and in so doing diminishes the efficacy of ICIs in elderly subjects. We performed a meta-analysis to compare the efficacy of ICIs between younger and older patients. PubMed and the ASCO databases were searched up to September 2015. We included randomized controlled trials (RCTs) of ICIs (ipilimumab, tremelimumab, nivolumab and pembrolizumab) reporting subgroup comparison of overall survival (OS) and/or progression-free survival (PFS) based on age cutoffs. The summary hazard ratio (HR) and 95% confidence interval (CI) were calculated. A total of 5265 patients from nine RCTs of ICI were included. When patients are dichotomized into younger and older groups with an age cut-off of 65–70years, ICIs improved OS in both younger (HR, 0.75; 95% CI, 0.68–0.82) and older (HR, 0.73; 95% CI, 0.62–0.87) groups. An improvement in PFS was observed in younger (HR, 0.58; 95% CI, 0.40–0.84) and older (HR, 0.77; 95% CI, 0.58–1.01) patients. Subgroup analyses according to ICI and tumor type showed a consistent survival benefit in both younger and older groups except for the subgroup of older patients treated in 4 trials of anti-programmed cell death protein-1 (PD-1) monoclonal antibody (HR, 0.86; 95% CI, 0.41–1.83). A benefit in OS with ICIs was significant in both younger and older patients with a cut-off age of 65–70years.